The Effect of the Digitalization System and Clearance in Process on Service Quality and its Implications on the Accountability of Loading and Unloading Services at Cirebon Port - Lesmana, Eri Juhaeri; Simanjuntak, Marihot; Gusti, Ayudhia Pangestu (Dinasti International Journal of Digital Business Management, 2025)
Digital transformation in the port sector is a strategic step to improve efficiency, transparency, and accountability in services. One concrete example of this transformation is the implementation of the Si-PDKT (Ship Document Inspection System) application, which is applied by the Cirebon Class II KSOP. This application aims to accelerate the clearance in process for ships and supports the improvement of service quality and accountability in loading and unloading services. However, in practice, various obstacles are still found, such as limitations in system integration, human resource readiness, and resistance to new technology usage. This study aims to analyze the effect of the digitalization system (X1) and the clearance in process (X2) on service quality (Y) and its implications for the accountability of loading and unloading services (Z) at Cirebon Port. The approach used is explanatory quantitative with data collection through questionnaires from port service users. Data analysis is carried out using Structural Equation Modeling (SEM) with the SmartPLS software, complemented by SWOT analysis to identify strengths, weaknesses, opportunities, and threats in the implementation of the Si-PDKT application. The results of the study show that the digitalization system and the clearance in process have a positive and significant impact on service quality. Furthermore, service quality acts as a mediating variable that strengthens the influence of the digitalization system and clearance in on the accountability of loading and unloading services. The SWOT analysis also reveals that the application of Si-PDKT has great potential to be optimized, especially through improved system integration, human resource training, and adaptive regulatory support. This research provides strategic contributions to the development of smart port-based port services and serves as a reference for KSOP and other port stakeholders in formulating policies to improve public services that are efficient and accountable in the digital era